PERAN SISTEM PENGENDALIAN MANAJEMEN PADA PRESTASI KARYAWAN BERDASARKAN KINERJA KARYAWAN(STUDI PADA KOPERASI SIMPAN PINJAM PRIMA ARTHA SEJAHTERA) - DYAH AYU FEBRIANA SEISARITA, DINAR (Jurnal Akuntansi AKUNESA, 2015)
ABSTRACTIn practice an organization both private and government management control system is a matter that role. This research was conducted on Koperasi Prima Artha Sejahtera. The role of the management control system is very significant or instrumental to the achievement of employees considered managers based on employee performance. This study used survey method to the manager of a business unit especially in the non-bank financial organization that is Koperasi. The hypothesis was tested using comparison of data collected from observations and interviews by comparing the data that already exist in the literature theories presented.Keyword: Management Control System, and Job Performance